Protesting Smoke: A Social and Political History of Vancouver Air Pollution in the 1950s and 1960s - Thiessen, Lee (Urban History Review / Revue d'histoire urbaine, 2017)
Growth-oriented local businesses and the city of Vancouver initiated efforts in the late 1940s and early 1950s to address the city’s air pollution problem. Despite generally improving dustfall measurements due to changing fuel use, industrial relocation, and steady city management of the issue, the coalition of air-quality reformers did not obtain broader regional or provincial government support until the late 1960s. Rather, public interventions prompted the provincial government to acknowledge air pollution as a formal political issue, and finally to take action. This article provides an account of air pollution in Vancouver and British Columbia in the 1950s and 1960s, highlighting the roles of social and economic groups and their interactions with political structures.